2002
DOI: 10.1177/10791102009002008
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the Wechsler Adult Intelligence Scale–III in Schizophrenia

Abstract: This report examines and compares the factor structure of the new edition of the Wechsler Adult Intelligence Scale (WAIS-III) in a sample of chronic schizophrenia and schizoaffective disorder outpatients (n = 120) and an age-matched sample of individuals drawn from the WAIS-III standardization sample (n = 200). Exploratory and confirmatory factor analyses similar to those reported by the developers of the scale suggested that a model of WAIS-III performance with correlated factors for verbal comprehension, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
36
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 24 publications
9
36
0
Order By: Relevance
“…The replication of the four-factor structure verifies the portability of WAIS-III across clinical boundaries, and demonstrates its psychometric integrity. The results of the current study are consistent with those suggested by Ryan and Paolo 10 and Dickinson et al 12 Examination of fit indices indicates that in both samples the two-factor models produced a substantially better fit than the singe-factor model. Although the four-factor model best fitted the data, the twofactor model was the most parsimonious in terms of the PNFI in both research samples.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The replication of the four-factor structure verifies the portability of WAIS-III across clinical boundaries, and demonstrates its psychometric integrity. The results of the current study are consistent with those suggested by Ryan and Paolo 10 and Dickinson et al 12 Examination of fit indices indicates that in both samples the two-factor models produced a substantially better fit than the singe-factor model. Although the four-factor model best fitted the data, the twofactor model was the most parsimonious in terms of the PNFI in both research samples.…”
Section: Discussionsupporting
confidence: 91%
“…In the examination of factor structure of WAIS-III in a schizophrenia sample, Dickinson et al used both EFA and CFA to indicate that the four-factor WAIS-III presented a significant improvement over other competing models but did not improve significantly over the fivefactor model in a schizophrenia sample. 12 However, whether the four-factor model of the WAIS-III Chinese version fits the data from schizophrenia and nonclinical samples in the Chinese mainland is unclear. For all of these reasons, the purpose of the present study was to evaluate the construct validity of the special four-factor structure of the WAIS-III Chinese version in a clinical sample of inpatients with schizophrenia as well as a sample of healthy adults by CFA.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of PIQ is significantly lower than VIQ, and the Processing Speed is the lowest of 4 indexes. The results are consistent with the past findings [9,[14][15][16][17][24][25][26][27].…”
Section: Discussionsupporting
confidence: 83%
“…The Wechsler Adult Intelligence Scale (WAIS) has been used exten sively to assess cognitive functions in patients with schizophrenia for both research and clinical practices [3,[13][14][15][16][17][18]. The Wechsler Adult Intelligence Scale-III (WAIS-III) has been updated from the Wechsler Adult Intelligence Scale-Revised (WAIS-R).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the remarkable stability of Wechsler profiles for autism samples over the various versions of the tests provides additional assurance that despite revisions, the associations among the subtests have remained largely the same. Therefore models were tested that only included the 11 traditional subtests without inclusion of the additional subtests added to the "III" versions of the child and adult tests.One, two, and three-factor models were examined in developing models for the current study, as most previous studies using CFA to examine the factor structure of the Wechsler Scales have evaluated these models (Burton, Ryan, Paolo, & Mittenberg, 1994;Burton, Sepehri, Hecht, VandenBroek, Ryan, & Drabman, 2001;Brown, Hwang, Baron, & Yakimowski, 1991;Dickinson, Iannone, & Gold, 2002;O'Grady, 1983;Plake, Gutkin, Wise, & Kroeten, 1987;Waller & Waldman, 1990). For the one-factor model, all of the subtests are specified to load on a single factor.…”
mentioning
confidence: 99%